Synthesis variables effect on TiO2/polyester fabrics photoactivity and stability (2016)
TiO2-SiO2 coatings on fabric samples were obtained by immersion of 9 cm2 of commercial polyester in a TiO2-SiO2 suspension. This suspension was prepared by adding TiO2 P25 to a silica matrix obtained from the hydrolysis of tetraethyl orthosilicate (TEOS). The aim of this work was to study the relationship between the immersion time of the fabric on the photocatalytic activity and stability of the coating against several cycles of use and washing. Obtained samples were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and infrared spectroscopy (FTIR-ATR). Evaluation of modified fabrics was performed by self-disinfection tests under 250W/m2 of simulated sunlight using E. coli as model bacteria. In general, all modified fabrics (except that obtained at 2h immersion time) inactivated bacteria in less than 120min and its regrowth was prevented for at least 24h after the disinfection tests. It was determined that low immersion time (3-4h) lead to active and stable fabrics to 3 cycles of use and washing, whereas higher immersion times (12h) lead to more active but unstable fabrics.